A Rare Case of Cervical Squamous Cell Carcinoma Concurrent with Sinonasal Inverted Papilloma: A Case Report - Hou XY; Peng CR; Zhang GN; Wang DF (Dove Medical Press, 2022)
Xiao Yu Hou,1 Chun Rong Peng,2 Guo Nan Zhang,2 Deng Feng Wang2 1School of Medicine, University of Electronic Science and Technology of China, Chengdu, People's Republic of China; 2Department of Gynecologic Oncology, Sichuan Cancer Hospital & Institute, The Affiliated Cancer Hospital, School of Medicine, University of Electronic Science and Technology of China, Chengdu, People's Republic of ChinaCorrespondence: Deng Feng Wang, Department of Gynecologic Oncology, Sichuan Cancer Hospital & Institute, The Affiliated Cancer Hospital, School of Medicine, University of Electronic Science and Technology of China, No. 55, Section 4, South Renmin Road, Chengdu, 610041, People's Republic of China, Tel +86 15982222707, Fax +86 28 85420116, Email wonderful_96@163.comIntroduction: Cervical cancer is the fourth most common malignancy in women worldwide, and sinonasal inverted papilloma (SIP) is a rare benign sinus tumor with characteristics including a destructive growth pattern, high recurrence rate, and common malignant transformation. Cervical squamous cell carcinoma (SCC) combined with SIP has not been reported thus far.Case Presentation: A 55-year-old woman was diagnosed with cervical SCC in our center and treated with concurrent radiochemotherapy. During the follow-up period after the completion of cervical cancer treatment, the progression of cervical squamous cell carcinoma was first considered because the squamous cell carcinoma antigen (SCCA) levels remained high and slowly increased. However, SIP was found after a detailed investigation. The SCCA levels returned to normal after surgery. Two months after the surgery, because SCCA slowly increased again, it was found that the SIP recurred. After additional surgical treatment, the SCCA level returned to normal.Discussion and Conclusion: First, SCCA is an important indicator for monitoring changes in cervical SCC. When the changes in SCCA levels are inconsistent with the prognosis of cervical SCC, we should be vigilant about considering the possibility of other diseases existing at other sites in the body, which might lead to the earlier detection and treatment of SIP. Second, We recommended that SCCA be used as a routine monitoring index for SIP. If available, SCCA1 and SCCA2 should be evaluated to provide a more detailed assessment. Finally, for a high recurrence rate of SIP, anti-HPV treatment might be considered to reduce the risk of recurrence.Keywords: cervical squamous cell carcinoma, inverted papilloma, squamous cell carcinoma antigen, human papilloma virus